An Alternative View of Jave la Grande: Approaches to Cartographic History and their Impact on the Interpretation of The Dieppe Maps - Worth, Howard (The Australian Association for Maritime History, 2011)
Over the past three decades there has been a significant change in the way cartographic history has been viewed, initially due to the writings of the late J. B. Harley, but increasingly to the continuing work of other American and European map historians. For this reason it is worth reviewing much of the current analysis of those early French cartographic works usually referred to as the Dieppe maps, and the various arguments presented as a result of that analysis about whether or not they include representations of Australia.